Aloin Preconditioning Attenuates Hepatic Ischemia/Reperfusion Injury via Inhibiting TLR4/MyD88/NF-κB Signal Pathway In Vivo and In Vitro. (20th November 2019) - Du, Yichao; Qian, Baolin; Gao, Lin; Tan, Peng; Chen, Hao; Wang, Ankang; Zheng, Tianxiang; Pu, Shilin; Xia, Xianming; Fu, Wenguang
Abstract : Background . Aloin exerts considerable protective effects in various disease models, and its effect on hepatic ischemia-reperfusion (HIR) injury remains unknown. This research is aimed at conducting an in-depth investigation of the antioxidant, anti-inflammatory, and antiapoptosis effects of aloin in HIR injury and explain the underlying molecular mechanisms. Methods . In vivo, different concentrations of aloin were intraperitoneally injected 1 h before the establishment of the HIR model in male mice. The hepatic function, pathological status, oxidative stress, and inflammatory and apoptosis markers were measured. In vitro, aloin (AL, C21 H22 O9 ) or lipopolysaccharide (LPS) was added to a culture of mouse primary hepatocytes before it underwent hypoxia/reoxygenation (H/R), and the apoptosis in the mouse primary hepatocytes was analyzed. Results . We found that 20 mg/kg was the optimum concentration of aloin for mitigating I/R-induced liver tissue damage, characterized by decreased serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Aloin pretreatment substantially suppressed the generation of hepatic malondialdehyde (MDA), tumor necrosis factor alpha (TNF- α ), and IL-6 and enhanced the hepatic superoxide dismutase (SOD) activities as well as glutathione (GSH) and IL-10 levels in the liver tissue of I/R mice; this indicated that aloin ameliorated I/R-induced liver damage by reducing the oxidative stress and inflammatory response. Moreover, aloin inhibited hepatocyte apoptosis and inflammatory response that was caused by the upregulated expression of Bcl-2, the downregulated expression of cleaved caspase3(C-caspase3), Bax, Toll-like receptor 4 (TLR4), FADD, MyD88, TRAF6, phosphorylated IKK α / β (p-IKK α / β ), and phosphorylated nuclear factor κ B p65 (p-NF- κ B p65).